Microbial Electrochemical Systems: Deriving Future Trends From Historical Perspectives and Characterization Strategies - Hernandez, Cesar A.; Osma, Johann F. (Frontiers in Environmental Science, 2020)
Microbial electrochemical systems (MES) can be described as a combination of technologies with the unique ability to use microorganisms to conduct the transformation between chemical- and electric- energy. This property holds the promise to offer an alternative to the use of fossil fuels in the generation of electricity, and hazardous compounds in the production of chemical products. In this review, the fundamental aspects to describe the mechanisms involved in the MES microbe-electrode interaction are presented. Furthermore, a detailed discussion on the current classification strategies is presented including the techniques used at distinctive characterization levels. Also, the implementation of a dual-iterative bibliographic analysis is presented. The first iteration of the bibliographic analysis was considered from a historical perspective, allowing to identify, in a systematic manner, the main research areas related to MES. In the second iteration, the previously identified areas were surveyed in order to obtain a representative sample for the analysis and identification of trends and main research objectives of MES technologies. The MES areas that displayed the highest growth rate value are those related to “wastewater”, “wastewater treatment” and “extracellular electron transfer”; while “system (configuration/application)” and “microbial fuel cell” reported the highest number of related documents.